2021
DOI: 10.1002/ctm2.373
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome of renal tubular epithelial cells induces kidney injury in acute hemolytic transfusion reactions

Abstract: Background Blood transfusion, a common basic supporting therapy, can lead to acute hemolytic transfusion reaction (AHTR). AHTR poses a great risk to patients through kidney function damage in a short time. Previous reports found that heme from destroyed red blood cells impaired kidney function, and NLR family pyrin domain containing 3 (NLRP3) inflammasome was augmented in case of kidney injury. However, the detailed mechanism regarding whether NLRP3 inflammasome is involved in kidney function injury in AHTR is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In addition, WBCs and the pro-inflammatory cytokines also contribute to reactive oxygen species (ROS) overproduction and oxidative damage [ 5 , 6 ]. Both pro-inflammatory cytokines and ROS are potential activators of nucleotide-binding domain-like receptor protein 3 (NLRP3) inflammasome, which is consistent of NLRP3, apoptosis-associated speck-like protein containing a CARD (ASC) and caspase-1, and promotes the maturation and release of pro-inflammatory cytokines (e.g., IL-1β and IL-18) [ [7] , [8] , [9] , [10] ]. Macrophages are the dominant inflammatory cells in the lungs, and play critical roles in sepsis-induced inflammation, oxidative stress and ALI [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, WBCs and the pro-inflammatory cytokines also contribute to reactive oxygen species (ROS) overproduction and oxidative damage [ 5 , 6 ]. Both pro-inflammatory cytokines and ROS are potential activators of nucleotide-binding domain-like receptor protein 3 (NLRP3) inflammasome, which is consistent of NLRP3, apoptosis-associated speck-like protein containing a CARD (ASC) and caspase-1, and promotes the maturation and release of pro-inflammatory cytokines (e.g., IL-1β and IL-18) [ [7] , [8] , [9] , [10] ]. Macrophages are the dominant inflammatory cells in the lungs, and play critical roles in sepsis-induced inflammation, oxidative stress and ALI [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the NLRP3 inflammasome has been linked to a multitude of both acute and chronic renal disorders ( Mulay, 2019 ; Liu et al, 2021 ). Animal studies have shown that inhibiting either TXNIP or NLRP3 can prevent acute kidney injury caused by rhabdomyolysis-induced ischemia-reperfusion injury ( Yuan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the NLRP3 inflammasome has been associated with the activation of other cell death mechanisms, including apoptosis and necroptosis, further highlighting its involvement in renal disease pathogenesis [ 93 ]. Inhibitors of the NLRP3 inflammasome, such as MCC950 and CY-09, have been shown to ameliorate renal injury and improve kidney function in various animal models of kidney disease [ 206 , 207 , 208 ]. However, the clinical efficacy of these inhibitors remains to be tested in human trials.…”
Section: Potential Therapeutic Interventions Targeting Immunometaboli...mentioning
confidence: 99%